2017
DOI: 10.1136/archdischild-2017-313355
|View full text |Cite
|
Sign up to set email alerts
|

Influence of early childhood burns on school performance: an Australian population study

Abstract: Most childhood burn injuries occur before the start of formal schooling. Children who are hospitalised for burns perform more poorly in CBT even after accounting for family and socioeconomic disadvantage. Rehabilitation of children with burn injuries must address school performance to decrease any long-term negative societal impact of burns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 17 publications
(13 reference statements)
2
19
0
Order By: Relevance
“…Our review of the literature identified seven previous studies that specifically examined the impact of unplanned hospital inpatient admissions on educational outcome. [1,2,4852] Consistent with our findings, O’Brien Caughy’s analysis of secondary data in the U.S.A. showed that inpatient hospital admissions during the first year of life was associated with lower scores on reading recognition, partially explained by differences in levels of maternal education and the home environment [1]. Kull et al tested the associations between child development at age five years and indicators of physical health during childhood (including acute conditions and unplanned hospitalisations) in a large national birth cohort of children in Boston U.S.A. [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review of the literature identified seven previous studies that specifically examined the impact of unplanned hospital inpatient admissions on educational outcome. [1,2,4852] Consistent with our findings, O’Brien Caughy’s analysis of secondary data in the U.S.A. showed that inpatient hospital admissions during the first year of life was associated with lower scores on reading recognition, partially explained by differences in levels of maternal education and the home environment [1]. Kull et al tested the associations between child development at age five years and indicators of physical health during childhood (including acute conditions and unplanned hospitalisations) in a large national birth cohort of children in Boston U.S.A. [2].…”
Section: Discussionmentioning
confidence: 99%
“…Azzam et al examined the influence of burn injuries in national standardised curriculum-based school tests among children aged 8–14 years in Australia. They found that the most childhood burn injuries occur during the pre-school years, and children who were hospitalised had lower performance on academic assessments, suggesting that rehabilitation programmes for children with burn injuries should also include educational support for children [52].…”
Section: Discussionmentioning
confidence: 99%
“…This will be a retrospective population-level case-comparison study of injured or chronically ill children (ie, diabetes, epilepsy, asthma or mental health conditions). These four health conditions and injury were selected as injuries are the leading cause of hospitalisation in Australia for children aged 1–18 years,17 and the four chronic health conditions represent the most common health conditions experienced by children in Australia18 that have previously been associated with having a detrimental impact on learning 2–9. This will be a retrospective epidemiological study of children aged ≤18 years at the date of admission for their index hospitalisation in New South Wales (NSW), Australia.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Any restrictions on the ability of a child to perform to the best of their ability at school may adversely affect their career prospects and long-term quality of life. Traumatic injury or the presence of a chronic health condition, such as diabetes, epilepsy, asthma or mental health conditions, can have an adverse impact on the child’s performance at school 2–9. Interruptions to education can have a cumulative effect, resulting in being less likely to complete school or attend university and potentially limiting future employment opportunities 10.…”
Section: Introductionmentioning
confidence: 99%
“…Burn injuries are common in children and can have a lasting impact on their physical and psychosocial health 1–3 . The care of paediatric burn injuries places a significant burden on the health system 4 .…”
Section: Introductionmentioning
confidence: 99%